AN ANALYSIS OF THE EFFECT OF EARNINGS PERSISTENCE, GOOD CORPOARATE GOVERNANCE, AND ACCRUAL COMPONENT TO EARNINGS QUALITY ON BANKING IN INDONESIA IN 2011-2015 - Himmah, Elok Faiqoh (Universitas Airlangga, 2018)
This study aims to examine empirically the effect of earnings persistence, good corporate governance, and the accrual component of the quality of earnings in the banking sector in Indonesia. Data analysis was performed using quantitative descriptive methodthat aims to provide an overview of the nature of things that took place at the time the research was done. The study sample consisted of 25 banks listed on the Indonesia Stock Exchange (IDX) with data for a period of 5 years (2011-2015). The results showed that the accrual component of earnings persistence and significant effect on the quality of earnings. The resulting value is significantly smaller than 0.05. While GCG no significant effect on the quality of earnings in the banking sector in Indonesia, where significant value is greater than 0.05. This Study contributes to the existing Earnings Persistence, corporate governance, accrual component and earnings quality literature in emerging markets. In addition, this study offers some useful insights for regulators and policy makers by testing the effect of Banking Indonesia's reforms on earnings quality